Metrological determination of inhomogeneous hydrodynamic compaction during unsaturated out-of-plane permeability measurement of technical textiles. (3rd April 2019) - Willenbacher, B.; May, D.; Mitschang, P.
Abstract: An out-of-plane permeability measurement system is presented that initially enables monitoring of inhomogeneous hydrodynamic compaction of textiles during impregnation. For this, it provides linear variable differential transformers (LVDTs) in combination with ultrasonic technology, allowing continuous tracking of total stack compaction, flow front progression and single layer displacement. From this data the non-linear distribution of fiber volume content ( V F ) along with the sample thickness can be derived. Hence, data required for the validation of corresponding numerical models is generated, which again allows accounting measured permeability to a certain V F . It can also be used for parameter studies regarding the influence of process- and material-related parameters on the processing behavior of technical textiles during liquid composite molding processes. Graphical Abstract: